The importance of Urban Afforestation: analysis from the mapping of Syzygium malaccense and Licania tomentosa species in the urban area of Itapuranga, Goiás (Brazil) - Souza, Josimar dos Reis de; Silva , Samara Cristina Azevedo; Reis, Laís Naiara Gonçalves dos (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The present work aimed to carry out a rereading of the work entitled “Survey of urban afforestation and evaluation of the environmental perception of the inhabitants of the city of Itapuranga-GO”, carried out by Rosilane de Faria and Valéria de Sousa, in 2012. the same areas that were mapped in 2012 were compared and evaluated, focusing on two species commonly seen on city sidewalks: Syzygium malaccense and Licania tomentosa, known as Oiti and Jambota; as well as a survey of the number of existing individuals was carried out. In addition, the existence of patterns was verified in the houses where the cataloged trees were found, given the fact that economic disparity is a factor in the formation of unequal spaces. The specimens located were georeferenced using a GNSS navigation device, model GarminEtrex Vista, and photographed in field work. Subsequently, a database was created in the laboratory with basic information to identify the individual: geographic coordinates, sector, street name, species height, scientific and popular name. As a result, the relevance of some tree species for the purpose of urban afforestation is discussed, in the same way that others are classified as not recommended. During the field incursions, a total of 954 individuals were catalogued, unevenly and disproportionately divided among the four surveyed sectors, considering that the trees found in squares and other areas were not computed. Finally, it was concluded that, contrary to expectations, the areas with the most trees are not the newest areas with the highest purchasing power, but the oldest sectors of the city, with a lower income population.